High compressive strength three component polyurethane composition for airport road patching
Patent Information
- Application Number
- CN202610432749.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-27
AI Technical Summary
但是,该聚氨酯组合物的异氰酸酯组分中只使用了MDI预聚物,在多元醇组分中只使用了蓖麻油,所得组合物具有过高弹性,因此尺寸稳定性不好,抗压强度和抗折强度仍不足够高
[0165]相应地,本发明的另一个主题是经固化的聚氨酯组合物。这样的组合物是在混合所述三种组分A、B和C并且将混合物固化之后而获得的。
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to polyurethane compositions, particularly three-component polyurethane compositions with high compressive strength, methods for their preparation, and their use in road repair, especially airport road repair. Background Technology
[0002] With the progress and development of the aviation industry, higher requirements have been placed on the repair standards of airport roads.
[0003] Early traditional repair materials were mostly cement-based. Although cement-based materials are more economical, it has been found in actual use that these products have low early strength and poor adhesion because airport road repair work is only open for 4-6 hours. At the same time, due to the large temperature difference between day and night outdoors, the concrete substrate will undergo significant shrinkage deformation, and under the high stress conditions of aircraft use, these products will crack again, which may even seriously affect flight safety.
[0004] In recent years, road repair materials based on polyurethane have begun to attract attention.
[0005] JP2022093978A discloses a polyurethane-based two-component curable composition and its use in road repair. The composition comprises a polyol (A) as the main agent, a compound (B) containing isocyanate groups (which is an organic isocyanate compound and / or a polyurethane prepolymer containing isocyanate groups) as a curing agent, and a fatty acid ester (C) that can be incorporated into component (A) or (B). The polyol (A) may contain castor oil-based polyols. The fatty acid ester (C) is incorporated into component (A) or (B) to achieve an anti-foaming effect. This document does not address airport road repair.
[0006] CN115417962A discloses a polyurethane composition for road repair, comprising component A and component B. Component A comprises a polyurethane prepolymer prepared from the following components by weight: 100 parts by weight of a first vegetable oil-based polyol and 80-200 parts by weight of an aromatic polyisocyanate. Component B comprises 100 parts by weight of a second vegetable oil-based polyol, 50-150 parts by weight of a polyether polyol, 5-30 parts by weight of a plasticizer, and 0.5-5 parts by weight of a coupling agent. The volume ratio of component A to component B is 1:0.5-2. This document does not address airport road repair.
[0007] CN101734885A discloses a polyurethane elastic self-leveling mortar, comprising component A, component B, and component C; component A comprises polyisocyanate; component B comprises castor oil and its derivatives; component C comprises any one or a mixture of more than one of quartz sand aggregate, gravel, or quartz powder; the ratio of component A:component B:component C is 1:1.5-2.5:12-18 by weight. This polyurethane elastic self-leveling mortar exhibits high elasticity, high tensile strength, high compressive strength, impact resistance, and cures in less than 2 hours; it is suitable for rapid repair of airports, roads, and highways. However, this polyurethane composition uses only MDI prepolymer in the isocyanate component and only castor oil in the polyol component, resulting in an excessively high elasticity, poor dimensional stability, and insufficient compressive and flexural strength.
[0008] Therefore, there is a need for a polyurethane composition with good overall performance that is particularly suitable for airport road repair. Summary of the Invention Invention Overview
[0010] In view of the problems existing in the prior art, the object of the present invention is to provide a three-component polyurethane composition that, after curing, has high mechanical strength and high early strength (especially compressive strength and flexural strength), good dimensional stability, good adhesion strength to road materials, and even high hardness and good chemical resistance, thus making it suitable for road repair, especially for airport road repair.
[0011] Another object of the present invention is to provide a method for preparing the three-component polyurethane composition, which is simple, low-cost and environmentally friendly.
[0012] Another object of the present invention is to provide a method for repairing roads, particularly airport roads, using the three-component polyurethane composition, which is simple, fast and environmentally friendly.
[0013] Unexpectedly, this invention has revealed that by combining highly functionalized polyols (a mixture of vegetable oil-based polyols and OH-terminated polyurethane prepolymers) with blended aromatic polyisocyanates (a mixture of polymeric aromatic polyisocyanates and NCO-terminated polyurethane prepolymers), more rigid segments and higher crosslinking degrees are obtained, thereby achieving a three-component polyurethane composition suitable for road repair, particularly airport road repair, with high mechanical strength, high early strength (especially compressive and flexural strength), good dimensional stability, and good adhesion to road materials. The compositions of this invention can achieve early compressive strength permissible for aircraft passage within 3 hours, making them particularly suitable for airport road repair work.
[0014] Therefore, in a first aspect, the present invention provides a three-component polyurethane composition comprising:
[0015] - Component A, which contains at least one polymeric aromatic polyisocyanate and at least one NCO-terminated polyurethane prepolymer; and
[0016] - Component B, which contains at least one vegetable oil-based polyol and at least one OH-terminated polyurethane prepolymer; and
[0017] - Component C, which contains at least one inorganic filler;
[0018] The composition contains at least 50% by weight of inorganic filler, based on the total weight of the composition.
[0019] In a second aspect, the present invention provides a method for preparing the three-component polyurethane composition.
[0020] In a third aspect, the present invention provides a method for repairing roads, particularly airport roads, using the aforementioned three-component polyurethane composition.
[0021] In a fourth aspect, the present invention provides the use of the three-component polyurethane composition for repairing roads, particularly airport roads.
[0022] Other objects and aspects provided by the present invention will become apparent from the following description. Invention Details
[0024] The three-component polyurethane composition of the present invention comprises a polyisocyanate component (component A), a polyol component (component B), and an inorganic filler component (component C).
[0025] The weight mixing ratio of component A to component B can be between 1:1 and 1:12, preferably between 1:1.2 and 1:5. The suitable weight mixing ratio of components A and B for each embodiment depends on the amount of polyisocyanate in component A and the amount of polyol in component B. Advantageously, the suitable mixing ratio is calculated such that, after mixing, there is a slight molar excess (e.g., 10 mol%) of isocyanate groups from the polyisocyanate relative to the hydroxyl groups from the polyol in the entire composition.
[0026] In the three-component polyurethane composition, the NCO value of component A is preferably 10-40%, particularly preferably 20-35%. The OH content of component B is preferably 1.5-10%, particularly preferably 3-7%. The NCO value represents the content of isocyanate groups (-NCO) per gram of sample, usually expressed as a percentage; the OH content represents the content of hydroxyl groups (-OH) per gram of sample, usually expressed as a percentage. The NCO value is determined according to GB / T 12009.4. The OH content is calculated by first determining the hydroxyl value according to GB / T 12008.3, and then using the following conversion formula: OH content = (hydroxyl value / 56.1) × 17 / 1000.
[0027] In a preferred embodiment, the three-component polyurethane composition according to the present invention comprises:
[0028] — Component A, which comprises:
[0029] a) at least one polymeric aromatic polyisocyanate, comprising 30 to 70% by weight of the total weight of component A;
[0030] b) At least one NCO-terminated polyurethane prepolymer, comprising 30 to 70% by weight of the total weight of component A;
[0031] — Component B, which contains
[0032] c) at least one vegetable oil-based polyol, comprising 30 to 70% by weight of the total weight of component B;
[0033] d) at least 30 to 70% by weight of at least one OH-terminated polyurethane prepolymer based on the total weight of component B; and
[0034] - Component C, which contains at least one inorganic filler.
[0035] The composition contains at least 50% by weight of at least one inorganic filler and components A and B together contain less than 5% by weight of inorganic filler, based on the total weight of the composition.
[0036] In a preferred embodiment, the composition comprises:
[0037] - 0.5% to 10% by weight, preferably 4% to 8% by weight, of component A based on the total weight of the composition;
[0038] - 1 to 30% by weight, preferably 5 to 20% by weight, of component B based on the total weight of the composition; and
[0039] - Component C, comprising 60 to 98.5% by weight, preferably 72 to 91% by weight, based on the total weight of the composition.
[0040] Some terms and definitions
[0041] Substance names beginning with "poly" such as polyols or polyisocyanates, in this document, indicate substances that formally contain two or more functional groups per molecule that appear in their name.
[0042] The term "polymer" herein includes, on the one hand, a collection of chemically homogeneous but different macromolecules in degree of polymerization, molecular weight, and chain length, obtained by polymerization reactions (polyaddition, addition polymerization, condensation polymerization). On the other hand, the term also includes derivatives of said collection of macromolecules from polymerization reactions, i.e., compounds that are obtained by reactions (e.g., addition or substitution) of predetermined functional groups on the macromolecules and are either chemically homogeneous or chemically incongruent.
[0043] The term "prepolymer" here generally refers to an oligomer or polymer used as an intermediate product in the production of polymers with higher molecular weights.
[0044] In this article, “molecular weight” is understood as the molar mass of a molecule (in grams per mole).
[0045] "Average molecular weight" refers to the number-average molecular weight (Mn) of a mixture of molecules in the form of oligomers or polymers, which is usually determined by gel permeation chromatography (GPC) relative to a polystyrene standard.
[0046] "Room temperature" or "ambient temperature" in this article refers to a temperature of 23°C.
[0047] A composition referred to as "multi-component" or "tri-component" means that the composition contains multiple or three different components that are stored in separate containers and are not mixed with each other until shortly before or during the application of the composition.
[0048] Aggregates, also known as aggregates, are granular materials that serve as a skeleton and filler in concrete or mortar.
[0049] Polyisocyanate component (component A)
[0050] The polyisocyanate component A used in the composition of the present invention comprises a blend of modified aromatic polyisocyanates, namely a mixture of at least one polymeric aromatic polyisocyanate and at least one NCO-terminated polyurethane prepolymer.
[0051] Suitable polymeric aromatic polyisocyanates that can be used can be polymeric forms of the following monomeric aromatic polyisocyanates: aromatic diisocyanates and / or triisocyanates, preferably selected from 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate (MDI), 2,4- and 2,6-toluene diisocyanate (TDI), 1,3- and 1,4-phenylene diisocyanate, 2,3,5,6-tetramethyl-1,4-diisocyanate, m- and p-phenylenedimethylene diisocyanate (m- and p-XDI), tetramethyl-1,3-phenylenedimethylene Diisocyanates (m-TMXDI), tetramethyl-1,4-phenylenedimethylene diisocyanate (p-TMXDI), bis-(1-isocyano-1-methylethyl)-naphthalene, naphthalene-1,5-diisocyanate (NDI), 3,3'-dimethyl-4,4'-biphenyl diisocyanate (TODI), dianisidine diisocyanate (DADI), tris(4-isocyanate phenyl)methane, 1,3,5-tris(isocyanate methyl)benzene and tris(4-isocyanate phenyl)thiophosphates and mixtures of their isomers and combinations thereof.
[0052] Preferably, the monomeric aromatic polyisocyanate is selected from 4,4'-, 2,4'-, and 2,2'-diphenylmethane diisocyanate (MDI) and 2,4- and 2,6-toluene diisocyanate (TDI) and mixtures of their isomers, particularly MDI and mixtures of their isomers, and the corresponding polymeric aromatic polyisocyanate is polymeric MDI, also known as PMDI. The polymeric aromatic polyisocyanate, particularly polymeric MDI, preferably has an NCO value (mass fraction) of 20-40%, more preferably 30-40%. The polymeric aromatic polyisocyanate, particularly polymeric MDI, has an average molecular weight of 100-1000, preferably 300-500.
[0053] Suitable polymeric aromatic polyisocyanates are commercially available, such as polymeric MDI from BASF under the trade name Lupranate M20S.
[0054] The polymeric aromatic polyisocyanates, especially those containing ureidone groups, isocyanurate groups, or imino groups, are particularly important. Oligomers containing a diazine dione group or a plurality of such groups; or containing an ester, urea, carbamate, biuret, urethane, carbodiimide, urea ketone imide, or Diazine trione groups or various difunctional or polyfunctional derivatives of these groups. In practice, such polyisocyanates typically represent mixtures of substances with different degrees of oligomerization and / or chemical structures. In particular, they have an average functionality of 2.1 to 4.0.
[0055] Compared with aliphatic polyisocyanates or their prepolymers, the aromatic polyisocyanates used in this invention can achieve a faster reaction rate, thereby forming crosslinks in a timely manner and making it less prone to cracking during the later aging process; in addition, it will not cause a significant increase in the TVOC content of the product.
[0056] To prepare the polyurethane composition according to the invention, a polymeric aromatic polyisocyanate and an NCO-terminated polyurethane prepolymer are blended to form polyisocyanate component A. Using such a blend of aromatic polyisocyanates facilitates obtaining more rigid segments, thereby improving the mechanical strength of the cured polyurethane composition, particularly compressive and flexural strength, as well as early mechanical strength (compressive and flexural strength) and hardness. Compared to polyurethane compositions using only one of the polymeric aromatic polyisocyanate and the NCO-terminated polyurethane prepolymer, the polyurethane composition using a combination of both achieves higher early compressive or early flexural strength, higher hardness, and a shorter open time.
[0057] Suitable NCO-terminated polyurethane prepolymers are polymer precursors with free isocyanate groups formed by reacting an excess of at least one monomer or polymeric polyisocyanate with at least one polyol; they can also be referred to as polyurethane prepolymers with isocyanate groups. The monomer or polymeric polyisocyanate used herein is preferably a monomer or polymeric aromatic polyisocyanate.
[0058] Specifically, the NCO-terminated polyurethane prepolymer can be obtained by reacting at least one polyol with at least one polyisocyanate using conventional methods, for example, at elevated temperatures, such as 40°C to 100°C, under the protection of an inert gas (e.g., nitrogen), and with moisture removed, optionally accompanied by a suitable catalyst, wherein the polyisocyanate is added in such a stoichiometric amount that its isocyanate groups are present in excess of the hydroxyl groups of the polyol. The reaction can be carried out at atmospheric pressure or a slightly elevated pressure.
[0059] Specifically, an excess of polyisocyanate may be selected such that the NCO value of the NCO-terminated polyurethane prepolymer obtained after reacting substantially all the hydroxyl groups of the polyol is 10 to 40%, preferably 20 to 35%, particularly preferably 23 to 24%. The free OH content is ≤0.1%.
[0060] Catalysts commonly used in the preparation of polyurethane prepolymers can be used, especially organotin (IV) compounds, organotitanates, or organozirconates. Complexes of tin (IV), bismuth (III), or zirconium (IV) can be used, especially those having ligands selected from alcohols, carboxyl groups, 1,3-diketones, oxinats, 1,3-keto esters, and 1,3-keto amidates, or compounds containing tertiary amino groups, especially, for example, 2,2'-dimorpholinodiethyl ether (DMDEE).
[0061] Organotin (IV) compounds are particularly preferred. Suitable organotin (IV) compounds are especially dialkyltin oxide, dialkyltin dichloride, dialkyltin dicarboxylate, and dialkyltin diacetylacetonate, such as dibutyltin oxide, dibutyltin dichloride, dibutyltin diacetate, dibutyltin dilaurate, dimethyltin dilaurate, dibutyltin diacetylacetonate, dioctyltin dioctyl oxide, dioctyltin dichloride, dioctyltin diacetate, or dioctyltin diacetylacetonate.
[0062] The amount of catalyst used can be in the range of 0.001 wt% to 1.0 wt%, particularly 0.005 wt% to 0.1 wt%, based on the total weight of the polyol and polyisocyanate as the starting reactants.
[0063] The polyols used to prepare NCO-terminated polyurethane prepolymers can be selected from polyether polyols, polyester polyols, vegetable oil-based polyols, styrene-acrylonitrile-grafted polyether polyols, polycarbonate polyols, poly(meth)acrylate polyols, polyhydrocarbon polyols, polyhydroxy functional acrylonitrile-butadiene copolymers, and mixtures of these polyols. Polyether polyols, polyester polyols, vegetable oil-based polyols, and combinations thereof are preferred.
[0064] The polyols mentioned above may have an average molecular weight of 250 to 30,000 g / mol, particularly 500 to 20,000 g / mol, and preferably have an average OH functionality in the range of 1.6 to 3.
[0065] Polyether polyols, also known as polyoxyalkylene polyols, polyoxyethylene polyols, or oligoether alcohols, are those that are polymers of substances such as ethylene oxide, 1,2-epoxypropane, 1,2- or 2,3-epoxybutane, oxetane, tetrahydrofuran, or mixtures thereof, optionally using a starting molecule having two or more active hydrogen atoms (e.g., water, ammonia) or a compound having multiple OH or NH groups (e.g., 1,2-ethylene glycol, 1...). 2- and 1,3-propanediol, neopentyl glycol, diethylene glycol, triethylene glycol, isomeric dipropylene glycol and tripropylene glycol, isomeric butanediol, pentylene glycol, hexanediol, heptanediol, octyl glycol, nonanediol, decanediol, undecanediol, 1,3- and 1,4-cyclohexanediol, bisphenol A, hydrogenated bisphenol A, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, glycerol, aniline, and mixtures of the aforementioned compounds are polymerized. Polyoxyalkylene polyols with low unsaturation (measured according to ASTM D-2849-69 and expressed in milliequivalents (meq / g) of unsaturation per gram of polyol) can be used, for example, by means of a so-called bimetallic cyanide complex catalyst (DMC catalyst), or polyoxyalkylene polyols with high unsaturation can be used, for example, by means of anionic catalysts (e.g., NaOH, KOH, CsOH, or alkali metal alkoxides).
[0066] Suitable polyether polyols can be selected from polyether diols and polyether triols, particularly from polyoxyethylene glycol, polyoxypropylene glycol, polyoxyethylene triol, polyoxypropylene triol, polyoxypropylene-polyoxyethylene glycol, and polyoxypropylene-polyoxyethylene triol, with polyoxypropylene glycol being preferred. The polyether polyol can have an average molecular weight in the range of 300 to 20,000 g / mol, preferably in the range of 400-5000 g / mol, and more preferably in the range of 500-1000 g / mol.
[0067] Polyester polyols can be polyesters having at least two hydroxyl groups and prepared by known methods, particularly by the condensation polymerization of hydroxycarboxylic acids or the condensation polymerization of aliphatic and / or aromatic polycarboxylic acids with di- or polyols.
[0068] Suitable polyester polyols include those prepared from di- to tri-ols (e.g., 1,2-ethylene glycol, diethylene glycol, 1,2-propanediol, dipropylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentanediol, glycerol, 1,1,1-trimethylolpropane, or mixtures thereof) with organic dicarboxylic acids or their anhydrides or esters (e.g., succinic acid, glutaric acid, adipic acid, trimethyl adipic acid, octanoic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, maleic acid, fumaric acid, dimer fatty acids, phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, dimethyl terephthalate, hexahydrophthalic acid, trimellitic acid and trimellitic anhydride, or mixtures thereof), as well as polyester polyols derived from lactones (e.g., ε-caprolactone).
[0069] Alternatively, vegetable oil-based polyols can be used, such as those derived from vegetable oils or through chemical modification of vegetable oils, such as epoxy polyesters and epoxy polyethers obtained by epoxidation of vegetable oils followed by ring-opening with carboxylic acids or alcohols, or polyols obtained by hydroformylation and hydrogenation of vegetable oils. Also suitable are polyols derived from degradation products or derivatives of vegetable oils obtained through degradation processes (e.g., alcoholysis or ozone decomposition) and subsequent chemical linkages (e.g., transesterification or dimerization). Suitable degradation products of vegetable oils are, in particular, fatty acids and fatty alcohols, as well as fatty acid esters, especially methyl esters (FAME), which can be derivatized, for example, by hydroformylation and hydrogenation to form hydroxy fatty acid esters.
[0070] The vegetable oil may be selected from castor oil, soybean oil, safflower oil, flaxseed oil, corn oil, sunflower seed oil, olive oil, rapeseed oil, sesame oil, cottonseed oil, palm oil, and tung oil, or combinations thereof.
[0071] In preparing NCO-terminated polyurethane prepolymers, in addition to the aforementioned polyols, small amounts of low molecular weight diols or polyols may be used, such as 1,2-ethylene glycol, 1,2- and 1,3-propanediol, neopentyl glycol, diethylene glycol, triethylene glycol, isomeric dipropylene glycol and tripropylene glycol, isomeric butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, undecanediol, 1,3- and 1,4-cyclohexanediol, hydrogenated bisphenol A, dimer fatty alcohols, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, glycerol, pentaerythritol, sugar alcohols such as xylitol, sorbitol or mannitol, sugars such as sucrose, other higher alcohols, low molecular weight alkoxylated products of the aforementioned diols and polyols, and mixtures of the aforementioned alcohols.
[0072] The aromatic polyisocyanate used in the preparation of the NCO-terminated polyurethane prepolymer can be selected from the polymeric aromatic polyisocyanates described above, or their corresponding monomeric aromatic polyisocyanates.
[0073] In principle, the NCO-terminated polyurethane prepolymer can be obtained from any form of reaction product. For example, the prepolymer can be a reaction product or mixture of products obtained by reacting at least one polyether polyol (e.g., polyether triol, polyether diol) and at least one polyisocyanate. It can also be obtained by first reacting at least one polyether polyol with each of at least one polyisocyanate separately, and then mixing the resulting reaction products.
[0074] In a particularly preferred embodiment, the NCO-terminated polyurethane prepolymer is the reaction product of at least one polyether polyol and at least one aromatic polyisocyanate. The at least one polyether polyol is preferably selected from polyether diols and polyether triols, particularly from polyoxyethylene glycol, polyoxypropylene glycol, polyoxyethylene triol, polyoxypropylene-polyoxyethylene glycol, and polyoxypropylene-polyoxyethylene triol, with polyoxypropylene glycol being particularly preferred. The aromatic polyisocyanate is preferably selected from MDI, TDI, and combinations thereof, particularly 4,4'-MDI.
[0075] Suitable NCO-terminated polyurethane prepolymers are commercially available, such as WANNATE8617 from Wanhua Chemical.
[0076] In component A, the weight ratio of at least one polymeric aromatic polyisocyanate and at least one NCO-terminated polyurethane prepolymer can be from 1:10 to 10:1, preferably from 1:5 to 5:1, more preferably from 1:1.5 to 1.5:1, and particularly about 1:1.
[0077] In polyisocyanate component A, the total content of at least one polymeric aromatic polyisocyanate and at least one NCO-terminated polyurethane prepolymer can be 60-100% by weight, preferably 70-95% by weight, based on the total weight of component A.
[0078] A small amount of modified monomeric aromatic polyisocyanate can also be used in component A, thereby liquefying the monomeric aromatic polyisocyanate, which facilitates use and stable storage, and can further improve the mechanical strength and early mechanical strength of the polyurethane composition as well as increase its hardness.
[0079] The modified monomeric aromatic polyisocyanate, also known as liquefied monomeric aromatic polyisocyanate, can be, for example, a urethane-modified (also known as a polyol-modified) monomeric aromatic polyisocyanate, a carbodiimide-modified monomeric aromatic polyisocyanate, a diazonium ketone imide-modified monomeric aromatic polyisocyanate, a urethane and diazonium ketone imide-modified monomeric aromatic polyisocyanate, especially the corresponding modified MDI and / or TDI.
[0080] Suitable modified monomeric aromatic polyisocyanates are, for example, liquefied MDI commercially available from BASF under the trade name LupranateMM103.
[0081] The content of modified monomeric aromatic polyisocyanate in component A can be 0-40% by weight, for example 5-30% by weight, based on the total weight of component A.
[0082] In a preferred embodiment, the modified monomeric aromatic polyisocyanate is the same as the monomeric aromatic polyisocyanate from which the polymeric aromatic polyisocyanate is derived, particularly selected from MDI and TDI and combinations thereof.
[0083] Component A may also contain aliphatic and / or cycloaliphatic diisocyanates incorporated into the prepolymer or present in small amounts in free form, particularly 1,4-butanediisocyanate, 2-methyl-1,5-pentanediisocyanate, 1,6-hexanediisocyanate (HDI), 2,2,4- and / or 2,4,4-trimethyl-1,6-hexanediisocyanate (TMDI), 1,10-decanediisocyanate, 1,12-dodecanediisocyanate, etc. Methylene diisocyanate, lysine diisocyanate or lysine ester diisocyanate, cyclohexane 1,3- or 1,4-diisocyanate, 1-methyl-2,4- and / or -2,6-diisocyanate cyclohexane (H6TDI), 1-isocyanate 3,3,5-trimethyl-5-isocyanate methylcyclohexane (IPDI), perhydrodiphenylmethane-2,4'- and / or -4,4'-diisocyanate (H 12 MDI), 1,3- or 1,4-bis(isocyanate methyl)cyclohexane, dimer or trimer fatty acid isocyanates.
[0084] Polyol component (component B)
[0085] The polyol component, namely component B, contains at least one vegetable oil-based polyol and at least one OH-terminated polyurethane prepolymer.
[0086] The plant oil-based polyols, as described above, are, for example, polyols obtained from plant oils or through chemical modification of plant oils, such as epoxy polyesters and epoxy polyethers obtained by epoxidation of plant oils followed by ring-opening with carboxylic acids or alcohols, respectively, or polyols obtained by hydroformylation and hydrogenation of plant oils. Also suitable are polyols obtained from degradation products or derivatives of plant oils obtained through degradation processes (e.g., alcoholysis or ozone decomposition) and subsequent chemical linkages (e.g., transesterification or dimerization). Suitable degradation products of plant oils are, in particular, fatty acids and fatty alcohols, as well as fatty acid esters, especially methyl esters (FAME), which can be derivatized, for example, by hydroformylation and hydrogenation to form hydroxy fatty acid esters.
[0087] The vegetable oil may be selected from castor oil, soybean oil, safflower oil, flaxseed oil, corn oil, sunflower seed oil, olive oil, rapeseed oil, sesame oil, cottonseed oil, palm oil, and tung oil, or combinations thereof.
[0088] Castor oil is preferred, such as that available from Huanghe Oils Co., Ltd. Castor oil primarily contains ricinoleic acid. Since ricinoleic acid molecules are not arranged in a single plane, they form a three-dimensional network structure after polymerization with isocyanates. The long-chain nonpolar fatty acids in castor oil give the prepared polyurethane repair material excellent hydrolysis resistance and flexibility, preventing foaming after prolonged immersion in water. Furthermore, it possesses excellent oil resistance, acid and alkali resistance, impact resistance, abrasion resistance, and good gloss. Castor oil also exhibits good fluidity; refined castor oil remains fluid at -22°C and does not become cloudy after rapid cooling to -50°C. This allows the final polyurethane repair material to withstand temperatures above 100°C and as low as -40°C.
[0089] The OH-terminated polyurethane prepolymer, also known as modified polyol, refers to a product with free hydroxyl groups obtained by prepolymerizing at least one polyisocyanate into at least one polyol.
[0090] The polyol used to prepare the OH-terminated polyurethane prepolymer may be selected from polyether polyols, polyester polyols, vegetable oil-based polyols, styrene-acrylonitrile-grafted polyether polyols, polycarbonate polyols, poly(meth)acrylate polyols, polyhydrocarbon polyols, polyhydroxy functional acrylonitrile-butadiene copolymers, and combinations thereof. The polyol preferably has an average molecular weight of 250 to 30,000 g / mol, more particularly 500 to 20,000 g / mol, and preferably has an average OH functionality in the range of 1.6 to 3.
[0091] Specifically, the OH-terminated polyurethane prepolymer can be obtained by reacting at least one polyol with at least one polyisocyanate using conventional methods, for example, at elevated temperatures, such as 40°C to 100°C, under the protection of an inert gas (e.g., nitrogen), and with moisture removed, optionally accompanied by a suitable catalyst, wherein the polyol is added in such a stoichiometric amount that its hydroxyl groups are present in stoichiometric excess relative to the isocyanate groups of the polyisocyanate. The reaction can be carried out at atmospheric pressure or a slightly elevated pressure.
[0092] Specifically, an excess of polyol may be selected such that the OH content of the OH-terminated polyurethane prepolymer obtained after reacting substantially all the isocyanate groups of the polyisocyanate is 1.5-10%, preferably 3-7%, and particularly preferably 4.5-4.95%. The free NCO content is ≤0.1%.
[0093] Catalysts commonly used in the preparation of polyurethane prepolymers can be used, especially organotin (IV) compounds, organotitanates, or organozirconates. Complexes of tin (IV), bismuth (III), or zirconium (IV) can be used, especially those having ligands selected from alcohols, carboxyl groups, 1,3-diketones, oxinats, 1,3-keto esters, and 1,3-keto amidates, or compounds containing tertiary amino groups, especially, for example, 2,2'-dimorpholinodiethyl ether (DMDEE).
[0094] Organotin (IV) compounds are particularly preferred. Suitable organotin (IV) compounds are especially dialkyltin oxide, dialkyltin dichloride, dialkyltin dicarboxylate, and dialkyltin diacetylacetonate, such as dibutyltin oxide, dibutyltin dichloride, dibutyltin diacetate, dibutyltin dilaurate, dimethyltin dilaurate, dibutyltin diacetylacetonate, dioctyltin dioctyltin oxide, dioctyltin dichloride, dioctyltin diacetate, dioctyltin dilaurate, or dioctyltin diacetylacetonate. For example, dibutyltin dilaurate catalyst available from Evonik under the brand name DABCO T-12 can be used.
[0095] The amount of catalyst used can be in the range of 0.001 wt% to 1.0 wt%, particularly 0.005 wt% to 0.1 wt%, based on the total weight of the polyol and polyisocyanate as the starting reactants.
[0096] In a preferred embodiment, the OH-terminated polyurethane prepolymer is a reaction product of at least one polyol selected from polyether polyols, polyester polyols, and mixtures thereof, and at least one polyisocyanate selected from aromatic polyisocyanates and aliphatic polyisocyanates and mixtures thereof. The polyether polyol is preferably selected from polyether diols and polyether triols, particularly from polyoxyethylene glycol, polyoxypropylene glycol, polyoxyethylene triol, polyoxypropylene-polyoxyethylene glycol, and polyoxypropylene-polyoxyethylene triol, especially polyoxypropylene glycol. The polyisocyanate is preferably selected from MDI and HDI, and mixtures thereof, particularly 4,4'-MDI.
[0097] In polyol component B, at least one vegetable oil-based polyol and at least one OH-terminated polyurethane prepolymer can be mixed in a ratio of 20:1 to 1:20, preferably in a ratio of 5:1 to 1.5:1. Using a larger proportion of vegetable oil-based polyol and a smaller proportion of OH-terminated polyurethane prepolymer, i.e., when the weight ratio of vegetable oil-based polyol to OH-terminated polyurethane prepolymer is greater than 1, the compressive strength, flexural strength, early compressive strength, early flexural strength, and hardness can be further improved.
[0098] In polyol component B, the total content of at least one vegetable oil-based polyol and at least one OH-terminated polyurethane prepolymer can be 60-100% by weight, preferably 80-98% by weight, based on the total weight of component B.
[0099] Inorganic filler components (component C)
[0100] For use as a road repair composition, the polyurethane composition of the present invention comprises at least 50% by weight of at least one inorganic filler as aggregate. To facilitate application and avoid undesirable reactions with the active ingredients in components A and B, it is suitable that the inorganic filler is wholly or substantially contained in another separate component (component C) of the polyurethane composition. Accordingly, components A and B may be substantially or completely free of inorganic filler, i.e., components A and B together contain less than 5% by weight of inorganic filler, based on the total weight of the composition.
[0101] The total content of inorganic fillers can be from 50% to 90% by weight, preferably from 65% to 85% by weight, based on the total weight of the composition.
[0102] The inorganic filler may be selected from one or more of the following substances: silica (e.g., quartz sand, quartz powder, silica fume); calcium carbonate, such as ground calcium carbonate (i.e., heavy calcium carbonate) or precipitated calcium carbonate (i.e., light calcium carbonate), which may be surface-treated by coating with fatty acids (especially stearic acid) or their salts or esters; barium sulfate (BaSO4, also known as barite); dolomite, wollastonite, clay, layered silicates (e.g., talc powder, mica powder), kaolin (e.g., calcined kaolin), alumina, cement, gypsum, fly ash, and slag.
[0103] The suitable particle size of inorganic fillers is less than or equal to 4 mesh, preferably 600 mesh to 6 mesh.
[0104] Silica is preferred as an inorganic filler. Silica fillers can be prepared or commercially available in various forms, such as quartz sand, quartz powder, and silica fume.
[0105] Silica fume, also known as microsilica powder, is a byproduct generated during the production of industrial silicon or ferrosilicon alloys. It is mainly composed of amorphous silicon dioxide (SiO2) and has a small particle size and a large specific surface area.
[0106] The main difference between quartz sand and quartz powder lies in their particle size. Quartz sand particles are typically between tens and hundreds of micrometers in size, while quartz powder particles are even smaller, generally between 1 and 10 micrometers in size.
[0107] Quartz sand has a much smaller specific surface area than quartz powder and silica fume, resulting in lower oil absorption and better flowability. Therefore, quartz sand is the preferred aggregate. The particle size of the quartz sand used is preferably 100 mesh to 6 mesh.
[0108] Quartz sand can have a single particle size distribution or be graded with different particle size distributions, such as 6-10 mesh quartz sand, 10-20 mesh quartz sand, 50-100 mesh quartz sand, 30-50 mesh quartz sand, and combinations thereof. The weight ratio of the four particle size distributions of quartz sand can be 1:(5-12):(4-10):(3-9). In a preferred embodiment, using graded quartz sand with different particle size distributions can achieve higher compressive strength, flexural strength, early compressive strength, early flexural strength, and hardness, and shorten the open time.
[0109] It is also preferable to polish one or more quartz sand fractions to improve the sphericity of the quartz sand, thereby better promoting the flow of the constituent components. For example, quartz sand with a size of 30-50 mesh can be prepared into polished round sand.
[0110] In a preferred embodiment, component C comprises silica filler, preferably comprising or composed of the following substances: silica filler, desiccant, lubricant additive, and rheology modifier.
[0111] The total weight of silica filler in component C can be 30-70% by weight, preferably 40-70% by weight, based on the total weight of component C.
[0112] Component C may use one or more silica fillers as described above, wherein the silica fillers may be selected from quartz powder, quartz sand and silica fume and combinations thereof, preferably quartz sand.
[0113] Component C preferably comprises graded quartz sand with different particle size fractions, as described above, thereby achieving higher compressive strength, flexural strength, early compressive strength, early flexural strength and hardness, and shortening the open time.
[0114] Preferably, one or more quartz sand fractions are polished to improve the sphericity of the quartz sand, thereby better promoting the flow of component C. For example, quartz sand with a size of 30-50 mesh can be prepared into polishing round sand. The amount of the polishing round sand can be 1-20% by weight, preferably 10-20% by weight, based on the total weight of component C.
[0115] Preferably, a desiccant is added to component C to facilitate moisture-proof storage. The desiccant may be selected from molecular sieves, calcium oxide, calcium chloride, sodium carbonate, potassium carbonate, calcium sulfate, and / or magnesium sulfate, particularly molecular sieves and / or calcium oxide, with molecular sieves being especially preferred. The content of the desiccant (particularly molecular sieves) based on the total weight of component C can be 0.5-10% by weight, preferably 1.5-5% by weight.
[0116] Advantageously, glass beads are added to component C as a lubricating additive to improve the flowability of component C in the initial stage. The amount of glass beads can be 1-20% by weight, preferably 5-15% by weight, based on the total weight of component C.
[0117] Garnet is preferably added to component C as a lubricating additive to advantageously improve the mixing of component C. The garnet preferably has a size of 16-80 mesh. The amount of garnet added can be 1-25% by weight, preferably 5-20% by weight, based on the total weight of component C.
[0118] Additionally, it is preferable to add rheology modifiers, particularly pyrolytic silica, to component C for reinforcement and thickening. The amount of pyrolytic silica added can be 1-20% by weight, preferably 5-15% by weight. The primary particles of the pyrolytic silica (i.e., fumed silica) used generally have a particle size of 7-40 nanometers.
[0119] In this document, particle size refers to the average particle diameter of primary particles. For spherical particles, the particle diameter is simply the diameter of the particle. For non-spherical particles, the particle diameter is determined as the average of the longest and shortest dimensions of the particle, where the longest dimension is the length of the longest line connecting one point to another on the particle profile, and the shortest dimension is the length of the shortest line connecting one point to another on the particle profile. These lines must also pass through the particle's center of gravity. Those skilled in the art can determine the particle diameter, for example, using a microscope, particularly an electron microscope (TEM) and a scanning electron microscope (SEM), by measuring a representative number of particles (e.g., 50 or more particles) using image evaluation methods.
[0120] The particle size is the mesh size, which can be determined, for example, by sieving.
[0121] Additional additives
[0122] Components A, B, and C may additionally contain other conventional additives, such as one or more additives selected from: catalysts, degassing agents or defoamers, drying agents (e.g., p-toluenesulfonyl isocyanate and other reactive isocyanates, molecular sieves, calcium oxide, calcium chloride, sodium carbonate, potassium carbonate, calcium sulfate, and / or magnesium sulfate), pigments, dyes, lubricating additives, rheology modifiers (e.g., thickeners, examples of which are shown in WO 02 / 48228). The types of thixotropic agents (“thixotropic agents”) described on pages 9 to 11 of A2 include urea compounds, polyamide waxes, bentonite, pyrolytic silica, adhesion promoters, surfactants (e.g., wetting agents, leveling agents), stabilizers resistant to heat, light, UV and oxidation, flame retardant additives, biocides (e.g., algaecides or fungicides), fibers (e.g., polyethylene fibers), plasticizers (e.g., sulfonamides, esters of organic carboxylic acids, esters of organic phosphoric acids and sulfonic acids, or hydrocarbons), and organic fillers (e.g., polyamides and PVC powders), preferably including defoamers, desiccants, catalysts for crosslinking polyurethanes, pigments, lubricating additives and rheology modifiers and combinations thereof.
[0123] The polyurethane composition may contain at least one catalyst for crosslinking the polyurethane. This catalyst particularly catalyzes the reaction of isocyanate groups with hydroxyl groups and / or water. Suitable catalysts include: basic nitrogen or phosphorus compounds, such as amines, imidazoles, pyridines, phosphazene-bases, hexahydrotriazine, amidine, guanidine, or biguanides; and metal compounds, especially organotin (IV) compounds, organotitanates, or organozirconates. Suitable amine catalysts are, for example, polyalkylene polyamines, N-ethyldiisopropylamine, N,N,N',N'-tetramethylalkylene diamine, 1,4-diazabicyclo[2.2.2]octane, 2,2'-dimorpholinodiethyl ether (DMDEE), and their derivatives having substituents on the morpholino ring. Triethylenediamine, for example, DABCO 33LV, available from Evonik, can be used.
[0124] The catalyst content is preferably in the range of 0.001% to 2% by weight, particularly 0.01% to 1.0% by weight, based on the whole composition.
[0125] In a preferred embodiment, component B comprises a catalyst for crosslinking polyurethane. The content of the catalyst may be 0.1-5% by weight, preferably 0.5-2% by weight, based on the total weight of component B.
[0126] To achieve an appearance similar to the road surface near the repaired road, it is preferable to add pigments, such as black pigments, particularly carbon black (especially industrially produced carbon black), to the polyurethane composition. Carbon black acts as a pigment to achieve a black composition and ultimately cures into a black repair material, and can also provide reinforcement. White pigments (such as titanium dioxide) and green pigments (such as chrome green) can also be added to achieve a gray polyurethane composition and, upon curing, a gray repair material. A suitable carbon black is, for example, Printex L6, available from Orion.
[0127] The pigments used can be added to one or more components of the composition. The specific type and amount of pigment depend on the color of the repair material to be achieved or the color of the road surface to be repaired.
[0128] Suitablely, components B and / or C contain pigments, preferably black pigments (especially carbon black), or white pigments (e.g., titanium dioxide) and green pigments (e.g., chrome green), thereby achieving a black or gray repair material.
[0129] In a preferred embodiment, carbon black is added to component B. The amount of carbon black can be 0.1-5% by weight, preferably 0.5-2% by weight, based on the total weight of component B.
[0130] Therefore, the polyurethane compositions of the present invention are substantially free of tar, bitumen, or asphalt. This means that such substances are preferably present in a content of less than 0.1% by weight, and in preferred cases, are completely undetectable.
[0131] An antifoaming agent may be used in component B to reduce bubbles generated during storage or reaction. The antifoaming agent may be selected from alcohols, hydrocarbons, paraffinic mineral oils, glycol derivatives, glycolates, acetates, and polysiloxane derivatives, such as BYK-055 from BYK Chemicals. The content of the antifoaming agent may be 0.1-5% by weight, preferably 0.5-3% by weight, based on the total weight of component B.
[0132] A desiccant may also be used in component B to facilitate moisture-proof storage. The desiccant may be selected from molecular sieves, calcium oxide, calcium chloride, sodium carbonate, potassium carbonate, calcium sulfate, and / or magnesium sulfate, particularly molecular sieves and / or calcium oxide, with molecular sieves being especially preferred, such as molecular sieve 3A available from Shanghai Jiuzhou Chemical Co., Ltd. The content of the desiccant, particularly the molecular sieve, may be 0.1-5% by weight, preferably 1.5-3% by weight, based on the total weight of component B.
[0133] As mentioned above, component C may contain desiccants, lubricating additives, and / or rheology additives.
[0134] Preparation method
[0135] The three-component polyurethane composition of the present invention can be prepared by separately mixing each component (components A, B and C) without removing moisture, forming respective mixtures, and storing or packaging them separately under inert gas protection.
[0136] Accordingly, the present invention also provides a method for preparing the three-component polyurethane composition, comprising separately mixing each component without removing moisture to form a corresponding mixture and storing or packaging it separately under an inert gas protection.
[0137] In particular, for polyisocyanate component A, it is essential to ensure that the components in component A are as water-free as possible and that no moisture may come into contact with the components during or after their preparation. This can be achieved through physical or chemical drying of the components and through operation under an inert gas (typically nitrogen).
[0138] The components are stored separately and are not mixed until just before or during the application of the composition. This process allows reactive components to be stored separately, which is beneficial for the storage stability of the composition.
[0139] For example, components A and B can be packaged separately in sealed containers, while component C can be first packaged in a moisture-proof bag and then placed in the sealed container. When using, first stir components A and B thoroughly, then add component C and mix further until homogeneous before use.
[0140] When all components are mixed, the polyisocyanate component A will react with the polyol component B, causing the composition to crosslink and cure.
[0141] application
[0142] The three-component polyurethane composition of the present invention has high mechanical strength and early strength, especially compressive and flexural strength, good dimensional stability, good adhesion to concrete, and even high hardness and good chemical resistance, as well as good resistance to acid erosion, alkali erosion and aviation kerosene erosion, thus making it suitable for road repair, especially airport road repair.
[0143] Therefore, the present invention provides the use of the three-component polyurethane composition for repairing roads, particularly airport roads. The compositions of the present invention are especially suitable for application to concrete pavements.
[0144] When used for road repair, components A, B, and C can be mixed together on-site and applied to the cracks or damage areas of the road during the pot life or open period of the polyurethane composition. The polyisocyanate component A and the polyol component B will react to form a polyurethane repair material.
[0145] The open period or usable time refers to the time after mixing the components, before the viscosity becomes too high to be further processed due to the progress of the crosslinking reaction, during which the polyurethane composition can be processed.
[0146] Accordingly, the present invention also provides a method for repairing roads, particularly airport roads, using the aforementioned three-component polyurethane composition, comprising the following steps:
[0147] - Mix all components of the polyurethane composition;
[0148] - The resulting mixture is applied to the damaged pavement during the open time of the polyurethane composition; and
[0149] - Curing the polyurethane composition;
[0150] or
[0151] - Mix all components during the application of the polyurethane composition; and
[0152] - Curing the polyurethane composition.
[0153] In a preferred embodiment, the repair method includes the following steps:
[0154] — Mix the above components A, B and C to form a polyurethane composition;
[0155] — During the open time of the polyurethane composition, the mixed polyurethane composition is applied to the road surface to be repaired, wherein the road surface to be repaired has been pretreated with an adhesion promoter or primer.
[0156] — Curing the polyurethane composition.
[0157] Pretreatment with an adhesion promoter or primer can improve the adhesion of the polyurethane composition to the road surface. For example, SikaEmaco-129 Rapid or WABO BONG, available from Sika, can be used as a primer.
[0158] Mixing can typically be accomplished using a static mixer or a dynamic mixer, such as a planetary agitator. During the mixing stage, it should be ensured that the components are mixed as uniformly as possible.
[0159] In order to evaluate the quality of the mixture from the perspective of appearance, it is advantageous that the components A, B and C have different colors, so that the components can be visually distinguished from each other and from the mixture.
[0160] For example, component A can be a clear liquid (such as, but not limited to, transparent or amber), component B can be a colored viscous liquid (such as, but not limited to, black or gray), and component C can be a grayish-white powder solid.
[0161] The cured polyurethane composition here is able to at least partially compensate for the movement of the road surface from, for example, thermal expansion through elastic extension, without causing cracking of the repaired road surface or separation from the surrounding road surface.
[0162] The compositions of the present invention have long durability, meaning they are stable for extended periods of storage. "Storage stable" means that a composition can be stored in a suitable container at room temperature and appropriate humidity for an extended period of time without suffering changes in its application or performance to a degree relevant to its use due to said storage.
[0163] The compositions of this invention can be applied to the road surface to be repaired using common pouring equipment. They can be laid manually or, when mixing large areas, can be laid using equipment similar to concrete mixing.
[0164] The compositions of the present invention can be applied in a temperature range between 5°C and 45°C, preferably in the range of room temperature, and are also cured under these conditions. Optionally, each of the individual components A, B, and C can be heated to a temperature, for example, in the range of 20°C to 60°C, more particularly 25°C to 40°C, before mixing.
[0165] Accordingly, another subject of the invention is a cured polyurethane composition. Such a composition is obtained by mixing the three components A, B, and C and then curing the mixture.
[0166] Beneficial technical effects
[0167] The three-component polyurethane composition of the present invention can achieve one or more, or even all of, the following beneficial properties:
[0168] 1) Good curing performance (preferred option: compressive strength of at least 35 MPa after curing in air for 7 days);
[0169] 2) High mechanical strength, especially high compressive strength (preferred option, at least 35 MPa after 7 days of air curing), high flexural strength (preferred option, at least 20 MPa), high early compressive strength (preferred option, at least 20 MPa after 3 hours of curing, where the early compressive strength is determined by 10% elastic deformation as the failure point), and high early flexural strength (preferred option, at least 10 MPa after 3 hours of curing).
[0170] 3) Excellent chemical resistance, especially resistance to acid corrosion, alkali corrosion and aviation kerosene corrosion;
[0171] 4) Good dimensional stability with a low rate of dimensional change, as specified in section 7.5 of JC / T 985-2017;
[0172] 5) High hardness (preferred design with a Shore hardness of at least 60);
[0173] 6) Good bond strength with concrete (preferably >2.5MPa);
[0174] 7) Shorter opening hours (preferred options are less than or equal to 6 hours, especially less than or equal to 4 hours). Detailed Implementation
[0175] Example
[0176] The present invention will be further illustrated below with reference to embodiments, but the present invention is not limited to these embodiments.
[0177] 1. Raw materials and their sources
[0178]
[0179] Other unspecified chemicals were commercially acquired.
[0180] 2. Test methods and equipment
[0181] Particle size and particle size: Sieve mesh size, determined by sieving, according to Sika Maple's standard test method TM-201 for particle grading, the specific steps are as follows: Select the required sieve according to SPEC requirements, clean it, and fix the sieves in order of aperture size on the base; weigh the combined sieve M1; weigh 200 grams of product (200 grams of raw material) on the top of the combined sieve; manually shake the sieve, if necessary, use a paintbrush to brush the material in the sieve until no material falls from the sieve; or put the combined sieve into a vibrator and vibrate for 2 minutes. For sieves larger than 70 mesh, manual grading can be done with a paintbrush until no material falls from the sieve; weigh the material residue on each sieve; calculate the residual percentage on each sieve.
[0182] Particle size: The average diameter of the primary particles. For spherical particles, the particle diameter refers to the diameter of the particle itself. For non-spherical particles, the particle diameter is determined as the average of the particle's longest and shortest dimensions, where the longest dimension is the length of the longest line connecting one point to another on the particle's profile, and the shortest dimension is the length of the shortest line connecting one point to another on the particle's profile. These lines must also pass through the particle's center of gravity. The average size of 50 particles was measured using a scanning electron microscope.
[0183] Compressive strength: Tested according to standard GB / T 17671-2021.
[0184] Early compressive strength: Tested according to standard GB / T 17671-2021. The 3h compressive strength of Type I is taken as the failure point at 10% elastic deformation.
[0185] Flexural strength: Tested according to standard GB / T 17671-2021.
[0186] Early flexural strength: Tested according to standard GB / T 17671-2021, flexural strength after 3 hours.
[0187] Shore hardness: Performed according to standard GB / T 2411-2008, using a type D Shore hardness tester.
[0188] Opening hours: Tests shall be conducted in accordance with the provisions of standard GB / T 1728-1979, Method A.
[0189] Chemical resistance: The prepared specimens were cured for 7 days under standard test conditions, immersed in 20% sodium hydroxide / 10% sulfuric acid / aviation kerosene for 3 days, and then the chemical corrosion was determined according to standard GB / T12954.1-2008. The standard test conditions were: temperature 23±2℃, relative humidity 50±5%, and circulating wind speed in the test area less than 0.2m / s; according to the provisions of 4.2 in GB / T12954.1-2008.
[0190] Adhesion strength: Tested according to the method specified in Appendix G of standard GB 50728-2011.
[0191] Dimensional stability: The rate of dimensional change was determined according to section 7.5 of JC / T 985-2017.
[0192] The NCO value was determined according to GB / T 12009.4.
[0193] The OH content is determined by first measuring the hydroxyl value according to GB / T 12008.3, and then calculating it using the following conversion formula: OH content = (hydroxyl value / 56.1) × 17 / 1000.
[0194] 3. Synthesis Example (Preparation of OH-terminated polyurethane prepolymer)
[0195] The four-necked reaction flask, equipped with a mechanical stirrer, thermometer, condenser, constant pressure dropping funnel, and nitrogen protection, was dried. It was then evacuated using a vacuum system and replaced three times with nitrogen (high-purity nitrogen (≥99.999%)) to maintain a slight positive pressure.
[0196] Polyoxypropylene glycol (number average molecular weight approximately 600, commercially available from BASF) was dehydrated at 105°C and a vacuum of ≤-0.098 MPa for 2 h, and then cooled to 45°C for later use. 4,4'-MDI (4,4'-diphenylmethane diisocyanate, BASF, brand name Lupronat® MS, purity ≥99.5%, NCO mass fraction approximately 33.5%) was melted at 45°C under dry nitrogen protection for later use.
[0197] Under nitrogen protection, 95 parts by weight of dehydrated polyoxypropylene glycol (water content ≤0.03%) were added to a reaction flask, stirred, and heated to 60°C using an oil bath. 5 parts by weight of molten 4,4'-MDI were slowly added dropwise through a constant-pressure dropping funnel over 30 minutes, with the addition temperature controlled to not exceed 65°C. After the addition was complete, 0.01 parts by weight of dibutyltin dilaurate catalyst (Evonik, brand name DABCO T-12) were added, and the temperature was raised to 75±2°C, and the reaction was maintained for 3.0 h. Subsequently, the reaction mixture was degassed for 30 minutes at 75°C and a vacuum degree ≤-0.095 MPa, then cooled to 40°C, and discharged to obtain an OH-terminated polyurethane prepolymer. The obtained prepolymer was a colorless to light yellow transparent viscous liquid with a hydroxyl content of 4.5%–4.8% (mass fraction) and a free NCO content ≤0.1%. The resulting OH-terminated polyurethane prepolymer can be used directly for subsequent applications.
[0198] 4. Preparation of three-component polyurethane compositions
[0199] Add the components of polyisocyanate component A to a 1L planetary stirred tank, after removing moisture, at room temperature and under vacuum (gauge pressure less than -90 kPa), according to the dosages and types shown in Table 1. Stir until homogeneous, then release the vacuum with dry nitrogen and discharge the product. Store the resulting product in a sealed container for later use.
[0200] Similarly, the components of polyol component B are stored for future use.
[0201] To prepare filler component C, each component in the mixture C is dried at room temperature under vacuum or under dry nitrogen protection, then packed into a moisture-proof bag under dry nitrogen protection and stored in a sealed container for later use.
[0202] The weight % composition of each composition in the examples and comparative examples is shown in Table 1 below, where the content of each component is shown as a weight percentage based on the total weight of the component.
[0203] Table 1: Composition of the compositions in the examples and comparative examples
[0204]
[0205] Parameter
[0206] The reference design uses existing cement-based repair material, SikaEmaco T288, which is available from Sika.
[0207] 5. Performance Test Results
[0208] Various properties of the compositions and materials in the above embodiments and comparative examples, as well as the materials in the reference examples, were tested according to the test methods described above. The results are listed in Table 2 below.
[0209] Table 2: Performance Test Results
[0210]
[0211] The results in Table 2 show that the polyurethane composition according to the present invention exhibits good curing behavior due to the use of compounded aromatic polyisocyanates to obtain more rigid segments, and the introduction of highly functionalized polyols to provide higher crosslinking. It also achieves high compressive and flexural strength after 7 days of air curing, high early compressive and flexural strength after 3 hours of curing, high hardness, and good dimensional stability. It is suitable for aircraft passage during the open time for airport road repair work.
[0212] In addition, the cured polyurethane composition also has excellent chemical resistance and can withstand the erosion of acids, alkalis and chemicals such as aviation fuels like jet fuel.
[0213] The polyurethane composition of the present invention exhibits good adhesion strength to concrete road material near the repair site after curing, and can bond permanently and firmly without cracking or detachment.
[0214] A comparison of the performance test results of Examples 1-6 and the reference proportions according to the present invention shows that the cement-based repair materials using existing technology achieve higher compressive strength, flexural strength, and hardness, but do not exhibit early strength, have a significantly longer open time, lower bond strength, and lower chemical resistance. After 20% sodium hydroxide erosion, the specimens turned white; after 10% sulfuric acid erosion, the specimens showed significant precipitation and severe corrosion marks; and after aviation kerosene erosion, the specimens discolored. Furthermore, the dimensional stability of the reference proportion repair materials is also poor. Due to the low early strength of the cement-based repair materials in the reference proportions, their bond strength to concrete is poor. Simultaneously, due to the large temperature difference between day and night outdoors, the concrete substrate will experience significant shrinkage deformation and detachment. Under the high stress conditions of aircraft use, such products will crack again, even seriously affecting flight safety.
[0215] A comparison of the performance test results of Examples 1-6 of the present invention with those of Comparative Example 1 of the prior art polyurethane repair material shows that, compared with the prior art polyurethane repair material, the composition of the present invention achieves higher compressive strength and flexural strength, as well as higher early compressive strength and early flexural strength, higher hardness, and significantly shorter open time.
[0216] As shown in Comparative Examples 2-5, when the combination of highly functional modified polyols according to the present invention with blended aromatic polyisocyanates is not used, good mechanical strength or early mechanical strength cannot be achieved, or high hardness is not achieved, and the open time is long, thus making it unsuitable for airport road repair.
[0217] A comparison of Example 1 and Comparative Example 2 shows that when only polymeric MDI is added to component A without the addition of NCO-terminated polyurethane prepolymer, the compressive strength and flexural strength are similar, but the early compressive strength, hardness, and open time are lower. A comparison of Example 1 and Comparative Example 3 shows that when only NCO-terminated polyurethane prepolymer is added to component A without the addition of polymeric MDI, the compressive strength, flexural strength, and early flexural strength are significantly lower, the hardness is also significantly lower, and the open time is longer.
[0218] A comparison of Example 1 and Comparative Example 4 shows that when only castor oil is added to component B without adding OH-terminated polyurethane prepolymer, the compressive strength, flexural strength, early compressive strength, and early flexural strength are all significantly lower, the hardness is also significantly lower, and the open time is longer.
[0219] A comparison of Example 1 and Comparative Example 5 shows that when only OH-terminated polyurethane prepolymer is added to component B without adding castor oil, the compressive strength, flexural strength, and early flexural strength are significantly lower, the hardness is also significantly lower, and the open time is longer.
[0220] In addition, compared with Example 1, the use of modified MDI to replace part of the polymeric MDI and NCO-terminated polyurethane prepolymer in Examples 2-4 can further improve mechanical strength, early mechanical strength and hardness.
[0221] A comparison of Examples 1 and 5 shows that higher compressive strength, flexural strength, early compressive strength, early flexural strength, and hardness can be achieved when using more castor oil and less OH-terminated polyurethane prepolymer.
[0222] A comparison of Examples 1 and 6 shows that using graded quartz sand can achieve higher compressive strength, flexural strength, early compressive strength, early flexural strength and hardness, and shorten the open time.
[0223] Therefore, only the three-component polyurethane composition according to the present invention, after curing, has high mechanical strength and high early strength (especially compressive strength and flexural strength), good dimensional stability, good adhesion strength to concrete, and even high hardness and good chemical resistance, and has an open time suitable for airport road repair work, thus making it suitable for road repair, especially for airport road repair.
Claims
1. A three-component polyurethane composition comprising: - Component A, which contains at least one polymeric aromatic polyisocyanate and at least one NCO-terminated polyurethane prepolymer; - Component B, which contains at least one vegetable oil-based polyol and at least one OH-terminated polyurethane prepolymer; and - Component C, which contains at least one inorganic filler; The composition contains at least 50% by weight of at least one inorganic filler, based on the total weight of the composition.
2. The composition according to claim 1, wherein the polymeric aromatic polyisocyanate is a polymeric form of the following monomeric aromatic polyisocyanates: aromatic diisocyanates and / or triisocyanates, preferably selected from 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate (MDI), 2,4- and 2,6-toluene diisocyanate (TDI), 1,3- and 1,4-phenylene diisocyanate, 2,3,5,6-tetramethyl-1,4-diisocyanate, m- and p-phenylenedimethylene diisocyanate (m- and p-XDI), tetramethyl-1,3-phenylenedimethylene diisocyanate (m-TMXDI), tetramethyl-1,4-phenylenedimethylene diisocyanate (p-TMXDI), bis-(1-isocyano-1-methylethyl)-naphthalene, naphthalene-1,5-diisocyanate (NDI), 3,3 The monomeric aromatic polyisocyanate is selected from 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate (MDI) and 2,4- and 2,6-toluene diisocyanate (TDI) and their isomers and combinations thereof; preferably, the monomeric aromatic polyisocyanate is selected from 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate (MDI) and 2,4- and 2,6-toluene diisocyanate (TDI) and their isomers and combinations thereof, particularly MDI and its isomers; the polymeric aromatic polyisocyanate, particularly polymeric MDI, preferably has an NCO value of 20-40%, more preferably 30-40%; and preferably has an average molecular weight of 100-1000, more preferably 300-500.
3. The composition according to claim 1 or 2, wherein the NCO-terminated polyurethane prepolymer is a polymer precursor having free isocyanate groups formed by reacting at least one monomer or polymeric polyisocyanate with at least one polyol, wherein the at least one polyol is preferably selected from polyether polyols, polyester polyols, vegetable oil-based polyols, styrene-acrylonitrile-grafted polyether polyols, polycarbonate polyols, poly(meth)acrylate polyols, polyhydrocarbon polyols, polyhydroxy functional acrylonitrile-butadiene copolymers, and combinations thereof; and the polyol preferably has an average molecular weight of 250 to 30,000 g / mol, particularly 500 to 20,000 g / mol, and preferably has an average OH functionality in the range of 1.6 to 3.
4. The composition according to claim 3, wherein the NCO-terminated polyurethane prepolymer is a reaction product of at least one polyether polyol and at least one aromatic polyisocyanate, wherein the at least one polyether polyol is preferably selected from polyether diols and polyether triols, particularly from polyoxyethylene glycol, polyoxypropylene glycol, polyoxyethylene triol, polyoxypropylene-polyoxyethylene glycol, and polyoxypropylene-polyoxyethylene triol; and the aromatic polyisocyanate is preferably selected from MDI, TDI, and combinations thereof.
5. The composition according to any one of claims 1-4, wherein in component A, the weight ratio of the at least one polymeric aromatic polyisocyanate and the at least one NCO-terminated polyurethane prepolymer is 1:10 to 10:1, preferably 1:5 to 5:1, more preferably 1:1.5 to 1.5:1, and particularly about 1:
1.
6. The composition according to any one of claims 1-5, wherein in component A, the total content of the at least one polymeric aromatic polyisocyanate and the at least one NCO-terminated polyurethane prepolymer is 60-100% by weight, preferably 70-95% by weight, based on the total weight of component A.
7. The composition according to any one of claims 1-6, wherein component A further comprises a modified monomeric aromatic polyisocyanate, preferably selected from urethane-modified monomeric aromatic polyisocyanates, carbodiimide-modified monomeric aromatic polyisocyanates, diazacyclobutane-imide-modified monomeric aromatic polyisocyanates, and urethane and diazacyclobutane-imide-modified monomeric aromatic polyisocyanates, wherein the content is preferably 0-40% by weight, more preferably 5-30% by weight; the monomeric aromatic polyisocyanate from which the modified monomeric aromatic polyisocyanate is derived is preferably the same as the monomeric aromatic polyisocyanate from which the polymerized aromatic polyisocyanate is derived, particularly selected from MDI, TDI, and combinations thereof.
8. The composition according to any one of claims 1-7, wherein the OH-terminated polyurethane prepolymer in component B is a product having free hydroxyl groups obtained by prepolymerization of at least one polyisocyanate in at least one polyol, wherein the at least one polyol is preferably selected from polyether polyols, polyester polyols, vegetable oil-based polyols, styrene-acrylonitrile-grafted polyether polyols, polycarbonate polyols, poly(meth)acrylate polyols, polyhydrocarbon polyols, polyhydroxy functional acrylonitrile-butadiene copolymers, and combinations thereof; and the polyol preferably has an average molecular weight of 250 to 30,000 g / mol, particularly 500 to 20,000 g / mol, and preferably has an average OH functionality in the range of 1.6 to 3.
9. The composition according to claim 8, wherein the OH-terminated polyurethane prepolymer is a reaction product of at least one polyol selected from polyether polyols, polyester polyols, and mixtures thereof with at least one polyisocyanate selected from aromatic polyisocyanates and aliphatic polyisocyanates and mixtures thereof, wherein the polyether polyol is preferably selected from polyether diols and polyether triols, particularly from polyoxyethylene glycol, polyoxypropylene glycol, polyoxyethylene triol, polyoxypropylene-polyoxyethylene glycol, and polyoxypropylene-polyoxyethylene triol; and the polyisocyanate is preferably selected from MDI and 1,6-hexamethylene diisocyanate (HDI) and combinations thereof.
10. The composition according to any one of claims 1-9, wherein the at least one vegetable oil-based polyol in component B is selected from vegetable oils and polyols obtained by chemical modification of vegetable oils, wherein the vegetable oil is preferably selected from castor oil, soybean oil, safflower oil, linseed oil, corn oil, sunflower oil, olive oil, rapeseed oil, sesame oil, cottonseed oil, palm oil and tung oil and combinations thereof, and is particularly preferably selected from castor oil.
11. The composition according to any one of claims 1-10, wherein in component B, the weight ratio between the at least one vegetable oil-based polyol and the at least one OH-terminated polyurethane prepolymer is 20:1 to 1:20, preferably 5:1 to 1.5:
1.
12. The composition according to any one of claims 1-11, wherein the total content of the at least one vegetable oil-based polyol and the at least one OH-terminated polyurethane prepolymer in component B is 60-100% by weight, preferably 80-98% by weight, based on the total weight of component B.
13. The composition according to any one of claims 1-12, wherein the NCO value of component A is 10-40%, preferably 20-35%, and the OH content of component B is 1.5-10%, preferably 3-7%.
14. The composition according to any one of claims 1-13, wherein the at least one inorganic filler is selected from silica, calcium carbonate, barium sulfate, dolomite, wollastonite, clay, layered silicates, kaolin, alumina, cement, gypsum, fly ash, and slag, and combinations thereof, preferably selected from silica, wherein the particle size of the inorganic filler is preferably less than or equal to 4 mesh, more preferably 600 mesh to 6 mesh; the silica is preferably selected from quartz sand, quartz powder, and silica fume, and combinations thereof, particularly quartz sand, wherein the particle size of the quartz sand is preferably 6 mesh. Up to 100 mesh, the quartz sand is preferably graded quartz sand with different particle size fractions, such as quartz sand selected from 6-10 mesh, 10-20 mesh, 50-100 mesh, 30-50 mesh and combinations thereof, preferably quartz sand with the above four different particle size fractions, wherein the weight ratio of the four fractions is preferably 1:(5-12):(4-10):(3-9), and one or more of the fractions are preferably polished round sand, especially 30-50 mesh quartz sand is polished round sand.
15. The composition according to any one of claims 1-14, wherein the total content of the at least one inorganic filler is 50% to 90% by weight, preferably 65% to 85% by weight, based on the total weight of the composition.
16. The composition according to any one of claims 1-15, wherein components A and B together contain less than 5% by weight of inorganic filler, based on the total weight of the composition.
17. The composition according to any one of claims 1-16, wherein the composition comprises: - Component A, comprising 0.5% to 10% by weight, preferably 4% to 8% by weight, based on the total weight of the composition; - 1 to 30% by weight, preferably 5 to 20% by weight, of component B based on the total weight of the composition; and - Component C, comprising 60 to 98.5% by weight, preferably 72 to 91% by weight, based on the total weight of the composition.
18. The composition according to any one of claims 1-17, wherein the composition further comprises one or more additives selected from: catalysts, defoamers, desiccants, pigments, dyes, lubricating additives, rheology modifiers, adhesion promoters, surfactants, stabilizers resistant to heat, light, UV and oxidation, flame retardants, biocides, fibers, plasticizers and organic fillers, preferably selected from catalysts, defoamers, desiccants, pigments, lubricating additives, rheology modifiers and combinations thereof.
19. The composition according to any one of claims 1-18, wherein the composition comprises a pigment, particularly component B and / or C comprising a pigment, said pigment preferably selected from black pigments (especially carbon black), or a combination of white pigments (e.g., titanium dioxide) and green pigments (e.g., chrome green), thereby achieving a black or gray repair material.
20. The composition according to any one of claims 1-19, wherein component B comprises additives selected from: catalysts for crosslinking polyurethane, defoamers, desiccants (particularly molecular sieves), and pigments (particularly carbon black) and combinations thereof, wherein the amount of carbon black added is preferably 0.1-5% by weight, more preferably 0.5-2% by weight, based on the total weight of component B.
21. The composition according to any one of claims 1-20, wherein component C comprises silicon dioxide, wherein the total weight of silicon dioxide is preferably 30-70% by weight, more preferably 40-70% by weight, based on the total weight of component C; the silicon dioxide is preferably selected from quartz sand, quartz powder and silica fume and combinations thereof, especially quartz sand, wherein the particle size of the quartz sand is preferably 100 mesh to 6 mesh, and the quartz sand is preferably graded with different particle size fractions, for example selected from 6-10 mesh quartz sand, 10-20 mesh quartz sand, 50-100 mesh quartz sand, 30-50 mesh quartz sand and combinations thereof, preferably quartz sand having the above four different particle size fractions, wherein the weight ratio of the four fractions is preferably 1:(5-12):(4-10):(3-9), and one or more of the fractions are preferably polished round sand, especially 30-50 mesh quartz sand is polished round sand.
22. The composition according to claim 21, wherein component C further comprises a desiccant (particularly a molecular sieve), a lubricating additive (particularly glass beads and / or garnet), a rheology modifier, and combinations thereof, wherein preferably pyrolytic silica is added to component C as a rheology modifier, the amount of pyrolytic silica added being preferably 1-20% by weight, particularly 5-15% by weight, based on the total weight of component C.
23. A cured polyurethane composition obtained by curing the three-component polyurethane composition according to any one of claims 1-22.
24. A method for preparing a three-component polyurethane composition according to any one of claims 1-22, comprising separately mixing each component without removing moisture, forming respective mixtures, and storing or packaging them separately under an inert gas atmosphere.
25. A method for repairing roads, particularly airport roads, using a three-component polyurethane composition according to any one of claims 1-22, wherein the road is, in particular, a concrete road, the method comprising the steps of: - Mix all components of the polyurethane composition; - The resulting mixture is applied to the damaged road surface within the open time of the polyurethane composition; and - Curing the polyurethane composition; or - During the open time of the polyurethane composition, all components are mixed while applying the polyurethane composition to the road to be repaired; and - Curing the polyurethane composition; The road surface to be repaired is preferably pretreated with an adhesion promoter or primer.
26. The method of claim 25, wherein the polyurethane composition is applied to the road surface to be repaired in a temperature range between 5°C and 45°C, preferably in the range of room temperature.
27. The use of the three-component polyurethane composition according to any one of claims 1-22 for repairing roads, particularly airport roads, wherein the roads are in particular concrete roads.
Citation Information
Patent Citations
Polyurethane elastic self-leveling mortar
CN101734885A
Two-part curable composition
JP2022093978A
Highly weatherable moisture-curable one-component polyurethane compositions
WO2002048228A2